[…] you feel there's nowhere left to go: the barriers to support among women who experience substance use and domestic abuse in the UK. Issue 2 (29th February 2020) - Fox, Sarah
Abstract : Purpose: Domestic abuse victimisation is a common experience among women with problematic substance use, but support provision for both issues is siloed within the UK. Research on the topic focuses on practitioner responses, dominating women's voices within research, policy and practice. As such, knowledge about women's experiences of help-seeking is missing. This study therefore aims to fill a gap in knowledge by exploring the lived experiences of supporting seeking among women impacted by domestic abuse and substance use. Design/methodology/approach: Semi-structured interviews were conducted with 12 women who had a history of co-occurring problematic substance use and domestic abuse. Influenced by interpretive phenomenological analysis and feminist research praxis, the study explored how women with dual needs navigated support and help seeking and the barriers they faced. Findings: The women reported the biggest barrier was the disconnect between substance use and domestic abuse support, including a gap in the communication of information. This resulted in them having to choose which of their needs to seek support for. None of the women received support for their combined experiences, and most of the women never received support for their domestic abuse experiences alone. Originality/value: This is the first piece of research from the UK to explore, in-depth, women's journey through support for their co-occurring substance use and domestic abuse victimisation. Previous research has not consulted with women to understand how they navigate the complex support systems available. This paper is, therefore, important, because it demonstrates the journeys to services these women take and the barriers they have to overcome.